Assessment of antimicrobial activity of different concentrations of Tinospora cordifolia against Streptococcus mutans: An in vitro study - Sankalp Agarwal; Priyadarshini H Ramamurthy; Bennete Fernandes; Avita Rath; Preena Sidhu (Wolters Kluwer Medknow Publications, 2019)
Background: The antimicrobial property of Tinospora cordifolia has been tested against a variety of microorganisms in the literature. The present study aimed to assess the antimicrobial activity of different concentrations of commercially available T. cordifolia powder against Streptococcus mutans. Materials and Methods: An in vitro study was undertaken in which extract of T. cordifolia was obtained using 100% ethanol by maceration. Seven different concentrations were prepared and tested against S. mutans in brain-heart infusion agar medium. Plates were incubated aerobically at 37°C for 48 h, and zone of inhibition was measured using Vernier caliper. 0.2% chlorhexidine and dimethylformamide were used as positive and negative controls respectively. The data were analysed by descriptive analytic tests. Results: The maximum antibacterial activity of T. cordifolia was observed with a volume of 40 μl at 2% concentration with a zone of inhibition of 19 mm. A 30 μl volume of 0.2% chlorhexidine showed a zone of inhibition of 28 mm, and no zone of inhibition was observed with dimethylformamide. Conclusion: Tinospora exhibited antimicrobial activity against S. mutans. However, it needs to be confirmed further with in vivo studies.